Optimalisasi Hasil Belajar melalui Pretest dan Posttest Menggunakan Gamifikasi pada Mata Kuliah Bahasa Indonesia - Hariyanto, Hariyanto; Tiofani, Stacy (Gurindam: Jurnal Bahasa dan Sastra, 2025)
This research aims to investigate how effective pretests and posttests with gamification in enhancing student learning outcomes in the Indonesian Language course. Learning Indonesian language is often perceived as less engaging, compulsory, theoretical, and comprising abstract concepts. The researcher involved 152 subjects across four different Indonesian language classes, administering pretests and posttests before and after the material was explained. Two types of gamification were employed: Mentimeter in one class and Quizizz for three classes. The results reveal that all classes demonstrated higher posttest scores compared to their pretest scores. This finding suggests that gamification helps students become more engaged, motivated, focused, and better understand the material, as reflected in improved learning outcomes in Indonesian language course.